Game Mengenal Pahlawan Nasional Menggunakan Construct 2 Berbasis Android Untuk Sekolah Dasar Kelas IV - Muhammad Irfan Annas; Jeki Kuswanto; arvin Claudy Frobenius; Wisnu Yudo Untoro (Infotek: Jurnal Informatika dan Teknologi, 2023)
Games are a popular entertainment medium for children in today's modern times. Several types of game genres can be found on a desktop or mobile basis. Game applications have a positive and a negative impact for users, especially on negative impacts for students, one of that is forgetting study time and many types of games function as entertainment media. Game media is not only an entertainment, but games can be used as learning media. Based on these factors, this research was conducted to determine the increase in the effectiveness of games as a media for learning the history of heroes for students. In this study, using construct 2 using HTML5 using a multimedia development life cycle (MDLC) method consisting of several sequences such as concept, design, material, manufacturing, testing to distribution. The output of the research is an Android mobile based game. The research resulted in an increase in the effectiveness of understanding the history of heroes for children by 17%, the factors assessed were in terms of appearance, in terms of menu completeness, in terms of content, and ease of use and benefits of the game